(3TQM GdQSGdg GdLjHjI dGHf GdeLOis - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3aEf GdhSGFd JTQa dTQa ebGUOgG hjdJMb HgG ai JYdjbGJ CMcGegG s
(3BNQgG (B:s
(3ef ZjQ GMJjGL Edi eG PcQg GdeJbOehf ef JfRjd GdeSGFd ai gPg GdBdg s
(3ajgG cKjQ ef GdQShe GdgfOSjI hHYV GdLOGhds
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B67 s
Keywords: (3Gdadcs